Review of the genus Miscophus Jurine, 1807 (Hymenoptera: Crabronidae: Crabroninae) of the Indian subcontinent with descriptions of two new species from southern India - Kumar, P. Girish; Mawadda, N.v. Ayisha; Terine, Joshua B.; Amal, S. (Zootaxa, 2024)
The digger wasp genus Miscophus Jurine, 1807 from the Indian subcontinent is reviewed with descriptions of two new species from India, Miscophus kaleshi Girish Kumar and Miscophus prasanthi Girish Kumar. A key to Miscophus of the Indian subcontinent is provided.